Assessment of Knowledge of Obstetric Danger Signs among Pregnant Women Attending a Tertiary Care Hospital - Mubeena H; Pracheth Raghuveer; Kiran R; Mohammed Ibrahim M; Mohammed Ibrahim Sherief A; Mazina Mohammed (Medsci Publications, 2019)
Introduction: Knowledge of obstetric danger signs among pregnant women is of paramount importance in improving maternal and fetal health outcomes. This study aims to determine the knowledge of danger signs among pregnant women seeking antenatal care in a tertiary care hospital. Methods: A cross-sectional study was carried out for two months among pregnant women who visited the antenatal clinic of a teaching hospital. A pre-tested and pre-designed proforma was used. Mean knowledge scores were computed and knowledge was classified into adequate and inadequate. Results: A total of 170 pregnant women fulfilling the inclusion criteria were included. Mean age of the study participants was found to be 26.40±4.14 years. Nearly 67.10% were aware of bleeding per vagina being a danger sign, 50.0% stated excessive vomiting as a danger sign, 23.50% knew that blurring of vision was a danger, while a mere 20.0% reported that convulsions were a danger sign. Overall, adequate knowledge (total knowledge score of 5 and above) was observed in 54.70% of the participants. Conclusion: Majority of the study participants had adequate knowledge of danger signs in pregnancy. However,, when knowledge about specific individual danger signs were further assessed, a high proportion had poor knowledge. The mean knowledge scores were found to be low.